Doc Hollywood - Johnson, Deborah D.; Solt, Susan; Caton-Jones, Michael (Warner Home Video, 1991)
Turns out to be witty charmer. Stone is a newly-minted MD whose medical fast lane cruise takes a small-town detour. Grady, South Carolina, Squash Capital of the South. is home to salt-of-the-earth folks who give the West coast-bound hotspot the seasoning he lacks.